Consequences of the treasury single account policy on the wealth of Nigerian commercial banks’ shareholders - Moses O; Ehalaiye D; Maimako S; Fasua K (Taylor & Francis (Routledge))
We examine the impact of the Nigerian government’s Treasury Single Account (TSA) policy to withdraw the funds of Ministries, Departments and Agencies from commercial banks. Following the economic policy uncertainty theory, we use an event study methodology to measure the impact of the TSA policy on shareholders’ wealth. Our results show that the announcements and subsequent final implementation of TSA policy caused negative abnormal returns and losses on the wealth of the commercial banks’ shareholders. The paper contributes to the literature on stock market reaction to policy announcements and the unintended consequences government policy can have in an emerging economy.
This is an Accepted Manuscript of an article published by Taylor & Francis in EMERGING MARKETS FINANCE AND TRADE on 16 January 2018, available online: http://www.tandfonline.com/10.1080/1540496X.2017.1356715
Keywords: event study; market reaction; Nigeria; Treasury Single Account (TSA); valuation; 1402 Applied Economics; 1502 Banking, Finance and Investment